A Neutrophil‐Inspired Supramolecular Nanogel for Magnetocaloric–Enzymatic Tandem Therapy. Issue 9 (21st January 2020) - Zhang, Qi; Wu, Jiaojiao; Wang, Jingjing; Wang, Xia; Wu, Chu; Chen, Mengwei; Wu, Qing; Lesniak, Maciej S.; Mi, Yongli; Cheng, Yu; Wang, Qigang
Abstract: Neutrophils can responsively release reactive oxygen species (ROS) to actively combat infections by exogenous stimulus and cascade enzyme catalyzed bio‐oxidation. A supramolecular nanogel is now used as an artificial neutrophil by enzymatic interfacial self‐assembly of peptides (Fmoc‐Tyr(H2 PO3 )‐OH) with magnetic nanoparticles (MNPs) and electrostatic loading of chloroperoxidase (CPO). The MNPs within the nanogel can elevate H2 O2 levels in cancer cells under programmed alternating magnetic field (AMF) similar to the neutrophil activator, and the loaded CPO within protective peptides nanolayer converts the H2 O2 into singlet oxygen ( 1 O2 ) in a sustained manner for neutrophil‐inspired tumor therapy. As a proof of concept study, both the H2 O2 and 1 O2 in cancer cells increase stepwise under a programmed alternating magnetic field. An active enzyme dynamic therapy by magnetically stimulated oxygen stress and sustained enzyme bio‐oxidation is thus shown with studies on both cells and animals. Abstract : METT its match : Nanogels are used as activatable and programmed regulatable neutrophil mimics for magnetocaloric‐enzymatic tandem therapy (METT) of cancer. The nanogel exhibits excellent chemphysical stability and biosafety. Magnetic activation and programmed upregulation of ROS in cancer cells can be fulfilled. This approach demonstrates successful singlet oxygen‐mediated cell/tumor proliferation inhibition.